2018
DOI: 10.1021/acs.jpcc.8b06645
|View full text |Cite
|
Sign up to set email alerts
|

Physical Origins of the Transient Absorption Spectra and Dynamics in Thin-Film Semiconductors: The Case of BiVO4

Abstract: Transient absorption (TA) spectroscopy is uniquely suited for understanding kinetic processes initiated by light over vast ranges of time. In combination with white light probes, the recorded differential absorption spectra can contain spectroscopic signatures characteristic of specific charge carrier population densities. However, disentangling the often-complex and convoluted spectra is made challenging without robust analysis methods relating the underlying physical mechanisms to the spectral components. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 50 publications
5
77
0
Order By: Relevance
“…In the study herein, we focus on a strong optical feature observed in transient spectroscopic studies of BiVO4 around its bandgap (λ = 470 nm, see Figure 2 below). [27][28][29] This feature appears spectroscopically analogous to a similar feature observed in α-Fe2O3 (λ = 580 nm), which we have previously suggested to originate from unoccupied oxygen vacancy states in α-Fe2O3. 30,31 There is however considerable dispute over the assignment of these features in both metal oxides, with other studies relating this spectral feature to photogenerated holes that undergo water oxidation, 27,[32][33][34][35] or suggesting this feature results from structural changes resulting from thermal effects of pulsed laser excitation.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…In the study herein, we focus on a strong optical feature observed in transient spectroscopic studies of BiVO4 around its bandgap (λ = 470 nm, see Figure 2 below). [27][28][29] This feature appears spectroscopically analogous to a similar feature observed in α-Fe2O3 (λ = 580 nm), which we have previously suggested to originate from unoccupied oxygen vacancy states in α-Fe2O3. 30,31 There is however considerable dispute over the assignment of these features in both metal oxides, with other studies relating this spectral feature to photogenerated holes that undergo water oxidation, 27,[32][33][34][35] or suggesting this feature results from structural changes resulting from thermal effects of pulsed laser excitation.…”
Section: Introductionsupporting
confidence: 79%
“…However in BiVO4, the energetics and the derivative-like nature of the spectral response suggest that the feature may be due to phenomena such as electroabsorbance effects, as suggested elsewhere. 28 Whilst further work is necessary to understand the exact spectroscopic origin of this optical feature, our experimental observations strongly correlate this spectral fingerprint to changes in the concentration of…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…[ 24 ] Typically, temperature‐induced changes in optical properties due to laser‐induced heating from carrier recombination are of critical importance to deconvolve in order to ascertain information related to excited carrier populations. [ 25 ] In this case, however, because we are comparing only CBO with and without Cu 1.5 TiO z , any changes in dynamics can be attributed to a change in electronic‐related components as the thermal properties of the films are assumed to be effectively identical.…”
Section: Resultsmentioning
confidence: 99%
“…The two detectors were used for simultaneous collection of the differential transmission (dT) and the differential reflection (dR) signal. The differential absorption (dA) signal was calculated using the following equation 33 i k j j j j y…”
Section: ■ Experimental Sectionmentioning
confidence: 99%